Digestibility of Nutrients as Influenced by Supplementation of Exogenous Fibrolytic Enzymes in Dry Non-pregnant Cows - Lunagariya, PM; Gupta, RS; Shah, SV; Patel, YG (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The study was planned to evaluate the effect of exogenous fibrolytic enzymes (EFE) supplementation for 56 days @ 240 mg/kg total mixed  ration (TMR) on digestibility of dry matter and nutrients in dairy cows. Six dry non-pregnant cows were assigned in each treatment with  and without EFE. The digestibility trial of seven days was conducted after 49 days of feeding. Dry matter and nutrients intake of cows  was not influenced by EFE. The supplementation of EFE had improved digestibility of dry matter, organic matter, crude fiber, neutral  detergent fiber, cellulose (p
Keywords: Cows; Digestibility; Exogenous fibrolytic enzymes; Total mixed ration; Weight gain